RESPON PENGGUNAAN PUPUK KASGOTCHAR DAN NPK MUTIARA TERHADAP PRODUKSI TANAMAN SAWI PUTIH (Brassica pekinensis L) VARIETAS TAHONO CR - Mufriah, Dini; Lisdayani, Lisdayani; Misdawati, Misdawati; Adriansyah, Adriansyah; Gusriani, Yunda; Diani, Diani (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2025)
The demand for white mustard in the market will continue to increase every year in line with economic growth, population growth, and growth in people's income, both for food, medicine, or other purposes. One of the efforts made to maintain and improve soil fertility is by providing organic materials such as manure to the soil. The purpose of this study was to determine the response to the use of kasgotchar fertilizer and pearl NPK fertilizer on the production of white mustard (Brassica pekinensis L) varieties of Tahono CR. This study used a Factorial Randomized Block Design with 2 factors: Factor l, namely the provision of Biochar kasgot fertilizer (K) with 3 levels, namely: K0 = Control (0 kg / plot), K1 = 10 tons / ha (1 kg / plot), K2 = 20 tons / ha (2 kg / plot). Factor 2, namely the provision of NPK fertilizer 16: 16: 16 (P) with 4 levels, namely: N0 = Control (0 kg / plot), N1 = 100 kg / ha (0.01 kg / plot), N2 = 200 kg / ha (0.02 kg / plot), N3 = 300 kg / ha (0.03 kg / plot). The parameters observed in this study include fresh weight per crop and production per hectare (kg). The results of the study showed that the use of kasgotchar and NPK fertilizers did not differ significantly on fresh weight per crop, production per hectare. The best treatment was the K2N3 treatment (kasgotchar with a dose of 2 tons / ha, and NPK with a dose of 300 kg / ha. Kasgotchar fertilizer can improve soil chemical properties.